The politics of social change in the Middle East and North Africa - Halpern, Manfred (ACLS Humanities E-Book., 1963)
"An attempt to analyze the cause and character of a profound revolution taking place from Morocco to Pakistan. This Report examines the forces, groups, ideas, and institutions now in motion and estimates the direction which politics may take in the future in the area. While the transformation here under study embraces both the pervasive nationalist revolution and the ensuing "revolution of rising expectations," its sources and ramifications are broader and run deeper than nationalism and its discontents: (1) a way of life 1300 years old is being destroyed by challenges for which it was almost entirely unprepared; (2) a social system with new values is taking the place of traditional society; (3) a different range of ideological choices has opened up for a new kind of elite; (4) new political instruments are at the elite's disposal; (5) the fact that new men are using new means to attain new ends in their attempts to deal with the politics of social change entails widespread revolutionary consequences."--Author's report.